The Effectiveness of Banten Culture-Based Ethnomathematics Teaching Materials for Learning the Pythagorean Theorem - Dinar Nirmalasari; Pinta Deniyanti Sampoerno; Makmuri Makmuri; Hepsi Nindiasari; Ade Nandang Mustafa (MASI Mandiri Edukasi, 2026)
Mathematics learning requires instructional approaches that enable students to understand abstract concepts through meaningful experiences. Ethnomathematics offers opportunities to connect mathematical ideas with cultural contexts; however, previous studies have largely focused on identifying mathematical concepts in cultural objects, while empirical evidence on the effectiveness of culture-based instructional materials remains limited. This study aimed to examine the effectiveness of Banten culture-based ethnomathematics video instructional materials in learning the Pythagorean Theorem. This study employed a posttest-only quasi-experimental design involving 60 eighth-grade students from a junior high school in Banten, Indonesia. The participants were divided into an experimental group ( ) and a control group ( ), with initial equivalence examined using Mid-Semester Test scores. Data were collected through a validated essay test and analysed using descriptive statistics, assumption tests, and an independent samples t-test. The experimental group achieved a higher mean posttest score (66.98) than the control group (46.11). The difference was statistically significant, , , with a large effect size (Cohen’s d = 0.95). The findings indicate that the developed instructional materials significantly improved students’ learning outcomes compared with conventional textbook-based instruction. However, the study was limited to one school and a relatively small sample. Future studies should involve broader contexts and additional learning variables.